2013
DOI: 10.1016/j.molcel.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Sustained PU.1 Levels Balance Cell-Cycle Regulators to Prevent Exhaustion of Adult Hematopoietic Stem Cells

Abstract: SUMMARY To provide a lifelong supply of blood cells, hematopoietic stem cells (HSCs) need to carefully balance both self-renewing cell divisions and quiescence. Although several regulators that control this mechanism have been identified, we demonstrate that the transcription factor PU.1 acts upstream of these regulators. So far, attempts to uncover PU.1’s role in HSC biology have failed because of the technical limitations of complete loss-of-function models. With the use of hypomorphic mice with decreased PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 46 publications
18
134
1
Order By: Relevance
“…These cells totally failed to reconstitute the bone marrow in the third transplantation. Chromatin Immunoprecipitation (ChIP) sequence data suggested that the reduction of PU.1 may stimulate active cycling, possibly resulting in the loss of HSCs [108].…”
Section: Transcription Factors Regulating Hscsmentioning
confidence: 99%
“…These cells totally failed to reconstitute the bone marrow in the third transplantation. Chromatin Immunoprecipitation (ChIP) sequence data suggested that the reduction of PU.1 may stimulate active cycling, possibly resulting in the loss of HSCs [108].…”
Section: Transcription Factors Regulating Hscsmentioning
confidence: 99%
“…Genome-wide studies have shown that hematopoietic genes such as PU.1 are actually primed in the HE by occupancy of TAL1/SCL and FLI1 to their regulatory regions and that a RUNX1-mediated reorganization of these factors is critical during EHT [44]. PU.1, on the other hand, contributes towards HSC maintenance by balancing the expression of cell-cycle regulators [45]. However, above all, PU.1 is a master regulator of later hematopoiesis and is required for commitment to the myeloid lineage since together with C/EBPα it controls the expression of the receptors for GM-CSF [46], and of CSF-1 which are critical cytokines for myelopoiesis [47,48].…”
Section: Developmental-stage-specific Runx1 and Pu1 Functionmentioning
confidence: 99%
“…Both RUNX1 and PU.1 contain distal regulatory elements harboring RUNX and ETS motifs [16,96], indicating that both genes are subject to autoregulation [44,45,89,97]. Using an inducible system, Lichtinger et al [44] showed that the induction of Runx1 leads to binding of RUNX1 to the proximal promoter and to a strong upregulation of its own expression.…”
Section: Developmental Regulation Of Runx1 and Pu1: One Regulates Thmentioning
confidence: 99%
“…Dysregulation of PU.1 leads to loss of lineage development and leukemia in vitro and in vivo (9,(26)(27)(28). Previous studies, however, have also demonstrated that PU.1 is required for the repopulation or self-renewal capacity of normal hematopoietic stem cells, and sustained PU.1 levels also balance cell cycle-associated regulators to prevent the exhaustion of adult HSC (8,15). These studies indicated that the presence of PU.1 activity may be required to favor the growth of myeloid leukemia stem cells.…”
Section: A B a Bmentioning
confidence: 99%
“…However, PU.1 exerts various functions at distinct hematopoietic stages. Although PU.1 is expressed at low levels in the early stage of hematopoiesis, it has an indispensable function in the maintenance of the HSC pool (6,15). Loss of PU.1 expression in mice leads to a weakening in the self-renewal capacity of long-term HSCs, which are then outcompeted by normal HSCs in bone marrow (8).…”
Section: Introductionmentioning
confidence: 99%